KAJIAN YURIDIS PENGEMBALIAN KERUGIAN KEUANGAN NEGARA SEBAGAI ALASAN MERINGANKAN PENJATUHAN PIDANA (Studi Kasus Putusan di Tindak Pidana Korupsi) - Arista Candra Irawati (Qistie Jurnal Ilmu Hukum, 2019)
Law No. 31 of 1999 concerning Eradication of Corruption Crimes as amended by RI Law No. 20 of 2001 concerning Amendment to Law No. 31 of 1999 in its application can not be separated from the offense / elements of acts against the law. One of the elements in Corruption Crimes is the existence of actions which are detrimental to the State. From one of these elements, as a form of existence due to criminal acts of corruption is detrimental to the State. Furthermore, in the process of returning the State's finances, the Prosecutor's Office has an obligation to return the State through replacement money. In accordance with Article 4 of the Corruption Criminal Act, it is stated, "Restoring state losses does not eliminate the responsibility of the perpetrators of corruption". In the application of returning the State's financial losses in the trial by the Defendant in the field of criminal procedural law, it has a very effective and efficient role, because it makes the reasons for the Public Prosecutor and the Case Inspectorate to provide criminal charges and convictions which are made easier for the Defendant as in the case study of criminal case decisions. corruption no. 118 / Pid.Sus / 2013 / PN.Tipikor.Smg on January 27, 2013 and court decision number: 125 / Pid-Sus-TPK / 2014 / PN.Smg on February 16, 2015. Keywords: Reduction of State Losses, Relieve, Criminal